A vaccine effective against Zika virus is theoretically possible but may not be delivered anytime soon - Taylor-Robinson AW (Research and Reports in Tropical Medicine, 2016)
Andrew W Taylor-Robinson Infectious Diseases Research Group, School of Medical and Applied Sciences, Central Queensland University, Rockhampton, QLD, Australia Abstract: Following the first report in May 2015 of the unexpected emergence of Zika in north east Brazil, there has been an explosive epidemic of this infection across Latin America. The outbreak has caused alarm among social and news media as to the virulence and transmission potential of the Aedes mosquito-borne virus. This debate is heightened by the proximity, both in time and distance, to the forthcoming Olympic Games to be held in Rio de Janeiro this August, provoking fears for the safety of athletes and spectators alike. The threat, real or perceived, is exacerbated by the movement between nations in the same or separate continents of persons who act unwittingly as asymptomatic carriers. Pregnant females are considered at greatest risk because microcephaly in newborn infants is linked to, if not yet proven as caused by, Zika infection. In February this year, the World Health Organization declared that further to the then unconfirmed association between the virus and the clinical manifestations of microcephaly and also Guillain-Barré syndrome, the Zika epidemic was a “public health emergency of international concern”. No anti-Zika therapy, vaccine or drug, is currently available and while the production of the former has now been prioritized by multiple funding agencies, the history of infectious disease vaccine development indicates that this may take several years to reach the market place. The fact that Zika is a close relative of yellow fever and Japanese encephalitis viruses, for both of which there are already effective vaccines, provides a rational basis for the fast-tracked laboratory-based preparation of a candidate vaccine. However, undertaking clinical trials on pregnant females provides ethical and practical hurdles to overcome before licensure is granted for public administration. Meanwhile, public health management strategies, including mosquito control programs to reduce breeding, are needed to limit the global spread of this re-emerging disease. Keywords: Zika, flavivirus, epidemic, vaccine